Do environmental taxes and green technological innovation represent the crux of environmental sustainability? Insights from OECD region with MMQR approach - Khan, Aleena; Sattar, Abdul; Alnafisah, Hind; Fatima, Nudrat (Frontiers in Environmental Science, 2025)
The significance of environmental taxes (ET) and green innovation has become paramount, particularly in light of the post-COP27 objectives and SDGs. This research contributes to the existing body of literature by exzuing the effects of environmental taxes (13), green innovation (SDG-9), green taxes, and financial development (SDG-17) on sustainable environmental quality. Furthermore, this study also investigated the moderating effect of green innovation on the relationship between environmental technologies and GHG emissions. The research utilized data from 36 OECD countries, covering the period from 1990 to 2020, employing DOLS (Dynamic Ordinary Least Square), FMOLS (Fully Modified Ordinary Least Square), and CCR (Canonical Cointegration Regression) methods to evaluate the long-run relationship among the variables. Further, Method of Moment Quantile Regression (MMQR) approach is also employed to reflect the diversity in the association patterns among variables at varying quantiles. Non-parametric BSQR (Bootstrapped Quantile Regression) approach is used to check the robustness of the results. The results demonstrate that the parameters remain consistent in terms of their differences, and there is evidence of long-term cointegration among the variables. The study revealed that the implementation of ET, environmental innovation, financial development, and trade openness has a significant impact on reducing GHG emissions. Moreover, green innovation moderates the association of environmental technologies and GHG emissions. Based on the estimations, the research offers pertinent policy recommendations to policymakers about environmental sustainability. It is crucial to include regulatory policies that promote the use of ET and the adoption of green innovative technologies and investments in the agenda of environmental technological progress to accelerate green technology innovation in OECD countries.